Prevalence and magnitude weight loss among collegiate wrestlers - Jagim, A. R.; Dobbs, W. C.; Horswill, C. A.; Twohey, E.; Fields, J. B.; Jones, M. T. (The Journal of Strength and Conditioning Research, 2025)
This study examined sex differences in weightlifting performance among youth athletes, emphasizing the role of fat-free mass (FFM), strength, and power. Fifty-three competitive weightlifters (28 male, 25 female) aged 13-15 years were evaluated using bioelectrical impedance analyses to estimate FFM, along with assessments of hand grip strength, squat jump (SJ) power, and isometric mid-thigh pull force. Competition outcomes for the snatch, clean & jerk (C&J), and total weight lifted were recorded. Male weightlifters demonstrated significantly higher absolute strength outputs compared with female weightlifters (p < 0.001). Regression analyses identified SJ power normalized to FFM as the strongest predictor of performance in male weightlifters across the snatch (r2 = 0.3742, p < 0.001), C&J (r2 = 0.3742, p < 0.001), and total (r2 = 0.3945, p < 0.001). In addition, results from the forward stepwise linear regression indicated that waist-to-hip ratio emerged as a significant, sex-specific predictor of C&J performance (p > 0.05). These findings underscore the importance of FFM and lower-body explosive strength in youth weightlifting success. However, inherent neuromuscular and biomechanical differences between sexes contribute to persistent performance gaps. The results support the implementation of sex-specific training strategies that target these unique physiologic profiles to optimize performance outcomes in youth weightlifters.